Transformasi Sosial Masyarakat Arab pada Masa Nabi Muhammad SAW Analisis Kritis dalam Perspektif Sejarah Kebudayaan Islam - Vivi Alvina Damayanti; Kholid Mawardi (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the social transformation of Arab society during the time of Prophet Muhammad SAW from the perspective of Islamic Cultural History. This research uses a qualitative method with a library research approach by examining relevant literature. The findings show that pre-Islamic Arab society was dominated by a tribal-based social system with high levels of social inequality. Social transformation began in the Meccan period through the message of monotheism, which changed the value system of society, and continued in the Medinan period through the establishment of an organized society based on brotherhood, justice, and equality. This transformation not only affected social and political aspects but also became the foundation for the development of Islamic civilization. Thus, the social transformation during the time of Prophet Muhammad SAW demonstrates Islam’s role as a multidimensional force of social change. Keywords: Social Transformation, Prophet Muhammad SAW, Arab Society, Islamic Cultural History